PENGARUH PENILAIAN KINERJA TERHADAP PRESTASI KERJA KARYAWAN (Studi pada Karyawan Bagian Produksi CV.Shuttlecock Nasional Kepanjen Malang) - Surya Rachma Aditya Eka Putra (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
These results indicate that simultaneously and partially on the performance of the production employees CV. National Shuttlecock significant effect on the dependent variable is the variable performance that can be seen from the value (sig) F <α ie 0.000 <0.05, and Adjusted R Square value shows the number of 34.636 which means that these variables accounted for 0.733 to variable performance . Partially, which can be seen from the results of t-test showed that the performance appraisal variables have a significance level of 0.000. Based on these calculations, it can be concluded that partial performance evaluation has a significant influence on employee performanceKeywords: Performance Appraisal, employee work achievements